16th AIAA Aviation Technology, Integration, and Operations Conference 2016
DOI: 10.2514/6.2016-4373
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Operational Constraints on the Near-Term Unmanned Aircraft System Traffic Management Supported Market

Abstract: An economic impact market analysis was conducted for 16 leading sectors of commercial Unmanned Aircraft System (UAS) applications that are expected to be supported in the near-future with the findings from the NASA UAS Traffic Management (UTM) project. Subject matter experts from industries were interviewed to validate concept of operations and market adoption assumptions for each sector. The market analysis was used to estimate direct economic impacts for each sector including serviceable addressable market, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Due to a number of applications of drones in the civil and construction industry, some researchers also considered the application of drones in construction safety (Irizarry et al, 2012). In general, the application of drones in the construction industry can be categorized into three main categories that include airborne surveying, safety, and quality inspection and progress monitoring (Vascik and Jung, 2016;Irizarry and Costa, 2016). Apart from many positive aspects of the drone, there are a number of risks associated with the application of drones in the construction industry.…”
Section: Improving Construction Safetymentioning
confidence: 99%
“…Due to a number of applications of drones in the civil and construction industry, some researchers also considered the application of drones in construction safety (Irizarry et al, 2012). In general, the application of drones in the construction industry can be categorized into three main categories that include airborne surveying, safety, and quality inspection and progress monitoring (Vascik and Jung, 2016;Irizarry and Costa, 2016). Apart from many positive aspects of the drone, there are a number of risks associated with the application of drones in the construction industry.…”
Section: Improving Construction Safetymentioning
confidence: 99%
“…This increased the operational payload capacity of available UAS for aerial applications while eliminating the previous barrier to entry that required remote pilots to have a private pilot certificate. This was previously identified as a major limitation for adoption of UAS in aerial application (Vascik and Jung, 2016).…”
Section: Exemption 18009mentioning
confidence: 99%
“…According to the Federal Aviation Administration (FAA) aerospace forecast for FY -2039(FAA, 2019, by the end of 2018, more than 277,000 nonmodel aircraft (non-recreational) UAS were registered in the U.S. Precision agriculture has been estimated as a significant sector of the overall UAS market in multiple economic evaluations (Jenkins and Vasigh, 2013;Vascik and Jung, 2016). However, several studies have shown that regulatory restrictions have impeded the adoption of UAS technology in the agricultural market (Freeman and Freeland, 2014;Vascik and Jung, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unmanned aircraft systems have rapidly proliferated commercial and private markets in the past five years with the Federal Aviation Administration forecasting over 440,000 commercial UAS and 3.5 million hobbyist UAS to be American Institute of Aeronautics and Astronautics in operation by 2021 [29]. The ConOps for a majority of the private and commercial small UAS applications focus on flight within a few hundred feet of the surface or in the vicinity of at-height infrastructure [30]. Federal Aviation Regulation Part 107 provides UAS with broad operating permissions to non-controlled airspace below 400 ft in altitude, and the FAA LAANC program may automate the process for UAS operators to gain authorization to operate in a specific controlled airspace.…”
Section: Interaction Of Odm Aircraft With Unmanned Aircraft Systemsmentioning
confidence: 99%